(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The widespread use of digital devices has led to an increasing prevalence of Digital Eye Strain (DES), characterized by ocular discomfort, dryness, and visual fatigue collectively known as Digital Eye Strain (DES). Objective: This study aimed to determine the prevalence and predictors of DES among university students and to propose interdisciplinary strategies for digital visual wellness. Methods: A cross-sectional analytical study was conducted among 300 university students using a structured questionnaire and basic ocular assessments. DES symptoms were evaluated using the Computer Vision Syndrome Questionnaire (CVS-Q), alongside Schirmer’s test and Tear Break-Up Time (TBUT) measurements. Statistical analysis was performed using SPSS v26 with Chi-square and logistic regression tests. Results: The prevalence of DES was 68.3%, higher among females (72%) than males (62%). Prolonged screen time (>6 hours/day), inadequate breaks, poor lighting, and reduced blink rate were significant predictors (p < 0.05). Mean TBUT was 7.1 ± 2.8 sec and mean Schirmer’s value 12.4 ± 3.6 mm, indicating mild tear instability. Behavioural factors and screen habits showed strong correlation with DES symptoms. Conclusion: Digital eye strain is highly prevalent among students, highlighting the need for interdisciplinary interventions combining optometric screening, ergonomic education, and behavioural modification.